Drosophila FIT is a protein-specific satiety hormone essential for feeding control - Sun, Jinghan; Liu, Chang; Bai, Xiaobing; Li, Xiaoting; Li, Jingyun; Zhang, Zhiping; Zhang, Yunpeng; Guo, Jing; Li, Yan (Nature communications, 2017)
Protein homeostasis is critical for health and lifespan of animals. However, the mechanisms for controlling protein feeding remain poorly understood. Here we report that in Drosophila , protein intake-induced feeding inhibition (PIFI) is specific to protein-containing food, and this effect is mediated by a fat body (FB) peptide named female-specific independent of transformer (FIT). Upon consumption of protein food, FIT expression is greatly elevated. Secreted FIT peptide in the fly haemolymph conveys this metabolic message to the brain, thereby promoting the release of Drosophila insulin-like peptide 2 (DILP2) and suppressing further protein intake. Interestingly, Fit is a sexually dimorphic gene, and consequently protein consumption-induced insulin release, as well as protein feeding behaviour, are also dimorphic between sexes. Thus, our findings reveal a protein-specific satiety hormone, providing important insights into the complex regulation of feeding decision, as well as the sexual dimorphism in feeding behaviour. Protein feeding is known to induce strong inhibition on further food intake, though the underlying mechanisms remain poorly understood. Here, the authors identify a protein-specific satiety hormone in Drosophila , and show that it suppresses feeding via promoting DILP2 release in the central nervous system.